Strategic warfare in the 21st century : is cyber-deterrence MAD? - Leonard, Ann-Sophie (2019)
The prefix cyber has become a major buzzword in the 21st century and nation states are now concerned with their ability to defend themselves in this virtual dimension. This dissertation contributes to the body of literature concerned with the evolving cyber-sphere in defence and military, by discussing nation states’ application of the strategic approach of mutual assured destruction (MAD) deterrence in the 21st century and the evolving cyber-dimension. While nuclear deterrence focused on deterring nuclear attacks, the parameters for cyber-deterrence remain ambiguous. To investigate deterrence, this dissertation will proceed in three parts. The first part introduces the meaning and magnitude of cyber in the 21st century by briefly comparing conventional and cyber-enabled warfare. In the second part, the origin of deterrence and the idea of MAD deterrence, including critiques of this strategic approach, are introduced. This understanding of deterrence is then used to examine the idea of a cyber-deterrence strategy and its ability to become like MAD. This includes a discussion of three limitations to the application of deterrence in cyber- space: territory, attribution and the problem of perception. The third part of this dissertation then proceeds by creating a catalogue of intervening dimensions (factors, topics and questions) of which nation state’s decision-makers must be aware when developing a cyber deterrence strategy. The dissertation concludes that cyber- deterrence is limited in scope thus to date MAD can only be tailored in theory as it relies on perception; or as mutually assured debilitation rather than destruction. If this is transferred into practice and strategic postures, the potential of cyber-deterrence is still limited. This dissertation further suggests that more aspects of the catalogue should be investigated. The author calls upon future research to add dimension to this catalogue.